Analisa Kepuasan Pelanggan Menggunakan Klasifikasi Data Mining - F Fauziah; Dedy Hartama; Irfan Sudahri Damanik (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2020)
The research objective was to obtain a model of rules in classifying the level of customer satisfaction at Indiis Cafe Pematangsiantar. By knowing the level of customer satisfaction, the owner of Indiis Cafe can improve the service if it is not good and further improve the service when the level of satisfaction is good. This study measures the level of customer satisfaction at Indiis Cafe Pematangsiantar. The method used in this study is the C4.5 Algorithm, where the data source used is a questionnaire / questionnaire given to customers at Indiis Cafe Pematangsiantar. The variables used include (1) Product, (2) Price, (3) Place (4) Promotion and (5) Service. The results of the study obtained 15 rules for the classification of customer satisfaction levels with 8 satisfied status rules and 7 unsatisfied rules. The C4.5 algorithm can be used in the case of customer satisfaction levels with an accuracy rate of 98.00%. From the results of the analysis is expected to be applied so that it can be used as a decision to improve service to customers.